Terpaan Media Instagram Pada Followers Klabinaria Subang : (Studi Deskriptif Kuantitatif Terpaan Media Instagram Pada Followers Klabinaria Subang) - Fitriyani Fitri (Journalism, Public Relation and Media Communication Studies Journal (JPRMEDCOM), 2022)
This study aims to determine how much Instagram media exposure is to Klabinaria Subang'sfollowers.This study uses the concept of media exposure by Rakhmat by measuring 3indicatorsof media exposure including frequency, attention and duration by Elvinaro. Thisresearch uses quantitative description research method. Respondents in this study wereInstagram followers @klabinariasubang, totaling 95 respondents. With sampling techniquenon probability samplinguses the Slovin formula, for data collection obtained through libraryresearch observations, questionnaires, and interviews. After doing the research, the resultsshowed that the value of the indicator of the frequency of exposure to the Klabnaria SubangInstagram media that of 95 respondents gave a high interval value with a percentage of68.84%, the value of the attention indicator of Klabnaria Subang Instagram media exposurethat of 95 respondents gave a high interval value with a percentage of 71.70% , the value ofthe Klabnaria Subang Instagram mediaexposure indicator value that out of 95 respondentsgave a high interval value with a percentageof 47.69%. Keywords : media exposure, instagram, followers